Henri Matisse - Brown, Kathryn (Kathryn J.) (Critical lives., 2021)
Henri Matisse's experiments with form and color revolutionized the twentieth-century art world. In this concise critical biography, Kathryn Brown explores Matisse's long career, beginning with his struggles as a student in Paris and culminating in his celebrated use of paper cutouts and stained glass in the last decade of his life. The book challenges various myths about Matisse and offers a fresh perspective on his creativity and legacy. Chapters explore the artist's enthusiasm for fashion and cinema, his travels, personal ties, interest in African art, love of literature, and willingness to challenge audience expectations. Through close readings of Matisse's works, Brown offers new insight into the artist's friendships and battles with dealers, critics, collectors, and fellow artists.